RESILIENSI INDIVIDU TERHADAP FEAR OF MISSING OUT (FoMO) DALAM PERSPEKTIF ETIKA TELEOLOGI ARISTOTELES - Trianto, Syaifullah Aji (Sanjiwani: Jurnal Filsafat, 2024)
Individual resilience is the ability possessed by someone to be able to recover and manage their emotions from the life problems they face. Fear of Missing Out (FoMO) is a psychological problem often experienced by social media users, in the form of anxiety due to missing trends, information, moments of other people's lives or other things outside themselves. Individuals with good self-resilience will be better able to overcome FoMO. There are various factors that influence individual resilience, for example, external factors can be in the form of cultural, religious or philosophical values embraced by the individual concerned. In this article, the author is interested in offering a view of Aristotle's teleological ethics in relation to the formation of individual resilience to FoMO. This research uses a phenomenological approach and elements of the philosophical method, namely: interpretation, critical reflection, holistic and descriptive. The results obtained show that Aristotle's teleological ethics emphasizes that humans as rational beings are fully responsible for their own lives, namely to actualize all the potential they have to act in harmony with moral virtues and solely for the sake of achieving the ultimate goal of happiness. Thus, there is no reason for individuals to worry about things outside themselves and ignore their own potential and goals.